Application of a new resource-constrained triage method to military-age victims. - Navin DM; Sacco WJ; McGill G; Navin, D Michael; Sacco, William J; McGill, Gill (Military Medicine, 2009)
Objective: Evaluate the resource-constrained, evidence-based, and outcome-driven Sacco Triage method (STM) for military-age victims of blunt, penetrating, and blast overpressure-like trauma.Methods: STM is based on a mathematical model of resource-constrained triage. Its objective is to maximize expected survivors given constraints on transport and treatment resources. STM uses estimates of time-dependent victim survival probabilities and expected deteriorations. A respiration, pulse, and best motor response (RPM) score predicts survivability. Logistic function-generated survival probability estimates from 99,369 military-age victims were assessed using calibration and discrimination statistics. The consensus building Delphi method was used to provide aggregate expert opinion on victim deterioration rates. The models were solved using linear programming. Rule-based (not requiring software) protocols were determined using a greedy algorithm for Iraqi combat scenarios, and simulations enabled comparison of STM to the widely known Simple Triage and Rapid Treatment (START) method.Results: RPM was an accurate predictor of survival probability, equivalent to the Revised Trauma Score and exceeding the Injury Severity Score. In 18 simulations, STM and STM rule-based protocols increased survivorship over START from 20% to an 18-fold increase.Conclusions: STM offers lifesaving and operational advantages for military-age victims of blunt, penetrating, and blast overpressure-like trauma.